2020
DOI: 10.1108/ijoem-02-2020-0134
|View full text |Cite
|
Sign up to set email alerts
|

Oil price shocks and emerging stock markets revisited

Abstract: PurposeThe study aims to understand the role of different streams of oil shocks (demand, supply and risk shocks) on the oil-importing and exporting countries' stock returns. The study also examines the impact of crude oil shocks across the economic regimes and market states. Besides, the role of the Global Financial Crisis (GFC) of 2008 in shaping the oil–stock relationship is also investigated.Design/methodology/approachThe authors revisit the impact of oil shocks on emerging equity markets by using the novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 52 publications
(107 reference statements)
0
8
0
1
Order By: Relevance
“…An increase in oil prices moves wealth from oil-importing countries to oil-exporting countries. Earlier studies show that oil price volatility as a source of uncertainty has a significant impact on the aggregate output of the country (Ferderer, 1996), corporate investment decisions (Alhassan, 2019; Henriques and Sadorsky, 2011; Maghyereh and Abdoh, 2020; Phan et al , 2019) and stock market returns (Das et al , 2020; Bahloul and Amor, 2021; Alqahtani et al , 2019). While many existing studies have explored the financial and economic effects of oil price volatility, little empirical analysis exists on the impact of oil price volatility on firms' profitability, and it is limited to the banking industry.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in oil prices moves wealth from oil-importing countries to oil-exporting countries. Earlier studies show that oil price volatility as a source of uncertainty has a significant impact on the aggregate output of the country (Ferderer, 1996), corporate investment decisions (Alhassan, 2019; Henriques and Sadorsky, 2011; Maghyereh and Abdoh, 2020; Phan et al , 2019) and stock market returns (Das et al , 2020; Bahloul and Amor, 2021; Alqahtani et al , 2019). While many existing studies have explored the financial and economic effects of oil price volatility, little empirical analysis exists on the impact of oil price volatility on firms' profitability, and it is limited to the banking industry.…”
Section: Introductionmentioning
confidence: 99%
“…Their study uses structural vector auto-regression and impulse responses to examine the dynamic (2019) observe high volatility in the stock markets due to movement in the oil prices. Das et al (2020) conclude that the oil and stock markets exhibit stronger relationship in the bearish markets. Demand shocks are positively related to the stock markets and supply shocks are negatively (Das et al, 2020).…”
Section: Empirical Studies 221 Dynamics Of Variables Of Research Afte...mentioning
confidence: 82%
“…As mentioned by Herrera et al (2019), among others, Ready's (2018) technique addresses several problems that researchers encountered in earlier models. Due to its appeal, Ready's (2018) methodology has gained popularity, and a line of work that evaluates the effects of disentangled oil shocks using this novel decomposition technique has emerged (see for instance Das et al, 2022, Anand & Paul, 2021, and Umar et al, 2021, among others. )…”
Section: Empirical Methodologymentioning
confidence: 99%
“…In a fairly recent study, Ready (2018) developed a novel decomposition technique to disentangle oil shocks and found that demand shocks are strongly positively related with market returns and economic output, whereas supply shocks have a strong negative relationship. Extending Ready's (2018) work, Das et al (2022) evaluated the stock markets of several emerging countries and showed that demand shocks are positively associated with the stock markets of several emerging countries, whereas supply shocks are negatively related, except in some oil-exporting countries. Anand and Paul (2021) reported similar findings, focusing only on the Indian stock market.…”
Section: Oil and The Stock Marketmentioning
confidence: 99%
See 1 more Smart Citation